I minori con disabilità e gli strumenti giuridici per l'effettività del diritto all'inclusione scolastica (Società e diritti, 2025)
In this contribution the Author analyses the Italian legislation on school inclusion between constitutional profiles and social and organisational implications.
Keywords: inclusion, students, disabilities